Plasma concentrations of SSRI/SNRI after bariatric surgery and the effects on depressive symptoms - Pasi, Patrick; Kröll, Dino; Siegfried, Alena; Sykora, Martin; Wildisen, Alessandro; Milone, Cristiana; Milos, Gabriella; Horka, Laura; Fischli, Stefan; Henzen, Christoph (Frontiers in Psychiatry, 2023)
Background Depression and treatment with antidepressants SSRI/SNRI are common in people with morbid obesity who are candidates for bariatric surgery. There is few and inconsistent data about the postoperative plasma concentrations of SSRI/SNRI. The aims of our study were to provide comprehensive data about the postoperative bioavailability of SSRI/SNRI, and the clinical effects on depressive symptoms. Methods Prospective multicenter study including 63 patients with morbid obesity and therapy with fixed doses of SSRI/SNRI: participants filled the Beck Depression Inventory (BDI) questionnaire, and plasma levels of SSRI/SNRI were measured by HPLC, preoperatively (T0), and 4 weeks (T1) and 6 months (T2) postoperatively. Results The plasma concentrations of SSRI/SNRI dropped significantly in the bariatric surgery group from T0 to T2 by 24.7% (95% confidence interval [CI], −36.8 to −16.6, p = 0.0027): from T0 to T1 by 10.5% (95% 17 CI, −22.7 to −2.3; p = 0.016), and from T1 to T2 by 12.8% (95% CI, −29.3 to 3.5, p = 0.123), respectively. There was no significant change in the BDI score during follow-up (−2.9, 95% CI, −7.4 to 1.0; p = 0.13). The clinical outcome with respect to SSRI/SNRI plasma concentrations, weight change, and change of BDI score were similar in the subgroups undergoing gastric bypass surgery and sleeve gastrectomy, respectively. In the conservative group the plasma concentrations of SSRI/SNRI remained unchanged throughout the 6 months follow-up (−14.7, 95% CI, −32.6 to 1.7; p = 0.076). Conclusion In patients undergoing bariatric surgery plasma concentrations of SSRI/SNRI decrease significantly by about 25% mainly during the first 4 weeks postoperatively with wide individual variation, but without correlation to the severity of depression or weight loss.